Comparison of radioiodine ablation rates between low versus high dose, and according to the surgeon's expertise in the low-risk group of differentiated thyroid cancer - Norouzi, Ghazal; Shafiei, Babak; Hadaegh, Farzad; Qutbi, Mohsen; Asli, Isa; Jafari, Esmail; Javadi, Hamid; Assadi, Majid (World Journal of Nuclear Medicine, 2021)
Radioiodine ablation following surgery is the accepted treatment for patients with differentiated thyroid cancer (DTC). Since that surgical volume and radioiodine dose can have impact on treatment outcome, we aimed to evaluate them on the treatment outcome of low-risk DTC patients. Low-risk DTC patients were classified into four groups, including (1) thyroidectomy was performed by thyroid surgeon and low-dose (1850 MBq [30 mCi]) radioiodine was administered (n = 17), (2) thyroidectomy was performed by thyroid surgeon and high-dose (3700 MBq [100 mCi]) radioiodine was administered (n = 10), (3) thyroidectomy was performed by general surgeon and low-dose radioiodine was administered (n = 22), and (4) thyroidectomy was performed by general surgeon and high-dose radioiodine was administered (n = 29). All patients were followed at least for 6 months and also for evaluation of treatment success, neck sonography, thyroid-stimulating hormone-off, thyroglobulin (Tg)-off, and anti-Tg-off tests were performed. Furthermore, two common radioiodine treatment-associated side effects, including dry mouth, and nausea/vomiting were assessed for all patients. Seventy-eight low-risk DTC patients (female: 70 [89.7%]; male: 8 [10.3%]) aged from 18 to 78 years old with mean of 41.96 ± 13.42 years were enrolled in this study. In total, the treatment was successful in 96.2% of patients. There was no significant difference in treatment success among groups (P > 0.05), while there was a significant association among administered activity and side effects. In low dose patients, only one patient complained from dry mouth; however, 11/39 patients who received high dose of iodine complained from dry mouth (P = 0.002). In addition, 9/39 high dose patients suffered from vomiting/nausea, while none of low-dose patients suffered from vomiting/nausea (P = 0.001). In low-risk DTC patients, surgical volume and amounts of radioiodine had no significant impact on treatment results; therefore, low dose radioiodine following thyroidectomy may be preferable to low-risk DTC patients to avoid side effects.
Keywords: Radioiodine ablation; surgical volume; thyroid cancer; thyroidectomy